Influence of Service Quality Dimensions in Commercial Banks of Bangladesh: Existing vs Expected (Global Journal of Management and Business Research, 2023)
The economy of a country is largely dependent on banking sector In this case Bangladesh is not exceptional Commercial banks of Bangladesh play a vital role in the economy making up one of the biggest providers of services in the economy In the current banking environment service quality is one of the main weapons which enables the banks to differentiate from each other Hence providing a better service quality is vital as banks have to compete for customers The primary focus of the study is to identify the gap between existing and expected service quality in terms of basic services advanced services cost and prestige customer satisfaction and customer loyalty issues Upon carrying out the study a total of 120 200 successful surveys samples were surveyed in different commercial banks of Bangladesh A questionnaire for such purpose was designed and different statistical methods were applied to analyse the collected data From the study of descriptive statistics it is found that the overall service quality in commercial banks in Bangladesh is moderate Whereas the sample t-statistics of the study shows that there is no significance difference between the existing and expected services of commercial banks of Bangladesh because the customer s demographic characteristics
Keywords: bank; customer; existing and expected; loyalty; quality; satisfaction; serive